Humanization of Death. Ethics of Accompanying the Patient in the Terminal State - Kowalski, Edmund (Studia Ecologiae et Bioethicae, 2020)
The aim of the article is to show the problem of humanization of death and related ethical challenges regarding accompanying the patient in the terminal state. In the event of insufficient therapeutic measures, the physician should take proper care of the dying person. The issue of humanization of death is described based on the writings of Elisabeth Kübler-Ross. First of all, it concerns the patient himself and his reaction to the perspective of death. Patient responses are very different and require a lot of patience from healthcare professionals and other caregivers. Also important are the ways of experiencing this situation by relatives and family, also taking part in the passing of the dying person, which can be expressed in shaking hope or lack of acceptance. The second part of the article discusses various ethical issues related to accompanying the dying: the ability to listen, assessment of the heritage of the past, mediation in the patient's responses, respect for the values professed by the patient, entering the cultural world of the dying, spiritual accompaniment, acceptance of defeats.